2009
DOI: 10.1289/ehp.0900596
|View full text |Cite
|
Sign up to set email alerts
|

Serum Polybrominated Diphenyl Ether (PBDE) Levels Are Higher in Children (2–5 Years of Age) than in Infants and Adults

Abstract: BackgroundPolybrominated diphenyl ethers (PBDEs) are used as flame retardants in many products and have been detected in human samples worldwide. Limited data show that concentrations are elevated in young children.ObjectivesWe investigated the association between PBDEs and age with an emphasis on young children from Australia in 2006–2007.MethodsWe collected human blood serum samples (n = 2,420), which we stratified by age and sex and pooled for analysis of PBDEs.ResultsThe sum of BDE-47, -99, -100, and -153 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
101
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(117 citation statements)
references
References 47 publications
15
101
0
1
Order By: Relevance
“…This is consistent with Penta-BDE congener concentrations in pooled Norwegian blood serum from 0-4 year-olds exceeding substantially those in adults (79). Likewise, in Australia, PBDE concentrations in pooled blood serum peaked at 2.6-3 years when breastfeeding has typically stopped (80). Similarly, a U.S. study showed higher PFOS and PFOA concentrations in pooled blood serum from 3-5 year olds compared to adults (81).…”
Section: Sources Of Variability In Concentrationsmentioning
confidence: 95%
“…This is consistent with Penta-BDE congener concentrations in pooled Norwegian blood serum from 0-4 year-olds exceeding substantially those in adults (79). Likewise, in Australia, PBDE concentrations in pooled blood serum peaked at 2.6-3 years when breastfeeding has typically stopped (80). Similarly, a U.S. study showed higher PFOS and PFOA concentrations in pooled blood serum from 3-5 year olds compared to adults (81).…”
Section: Sources Of Variability In Concentrationsmentioning
confidence: 95%
“…So, our result on no agedifference in PBDE burden seemed to be also explained by similar PBDE-exposure time. Recently, several studies reported the correlation between PBDE burden and age ( Haraguchi et al, 2009;Toms et al, 2008;Toms et al, 2009). In these literatures, however, the age-difference might suggest that PBDE burden depends heavily on exposure background and metabolism rather than exposure time (Johnson-Restrepo et al, 2005;Kunisue et al, 2007;Sjödin et al, 1999;Sjödin et al, 2000;Zhao et al, 2010).…”
Section: Association Between Pbde Levels In Semen and Patient Charactmentioning
confidence: 99%
“…Higher brominated congeners can undergo debromination to lower brominated congeners (Stapleton et al, 2004;Noyes et al, 2011). Thus, lower brominated congeners continue to be the predominant PBDEs found in samples worldwide (e.g., Lorber, 2008;Chen et al, 2009;Toms et al, 2009). Therefore, the environmental risk of PBDEs is still a matter of great concern.…”
Section: Introductionmentioning
confidence: 99%